PERLINDUNGAN HUKUM BAGI PEMEGANG POLIS PT. ASURANSI BINA DANA ARTA CABANG SAMARINDA ATAS KLAIM ASURANSI KENDARAAN RODA EMPAT DALAM INSIDEN KECELAKAAN - Rozi Pradani (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT The Protection of the law is a protection afforded to the subject of law in the form of a legal instrument, either of a preventive or repressive nature, whether written or unwritten. The Protection of the law can be attributed as a picture of the function of the law, namely the concept which can give justice, order, certainty, benefit, and peace. The Other opinion concerning the protection of the law is that it provides for the protection of human rights harmed by others and the protection is given to the public in order to enjoy all the rights granted by law. Whereas in claim is the demand for recognition of the fact that a person has the right to own or have over something. Overview coverage is a matter to note before the claim process is done by the insurer. Before processing the insurer claims need to know the insured coverage, in the insured overview there is data of the insured. The data becomes a reference by the insurer to compensate for losses suffered.